Symmetry detection based on multiscale pairwise texture boundary segment interactions - Mignotte, Max (Pattern recognition letters, 2016)
•An unsupervised procedure to local symmetry detection in natural images is proposed.•Achieved via a Hough-style voting approach made at different scales and coordinate spaces.•A final denoising scheme aims at removing noise and spurious local symmetries.•Experiments have been conducted on the recent extension of the Berkeley Segmentation Dataset.•The proposed method performs well compared to the state-of-the-art algorithms. [Display omitted] In this paper, we propose a new unsupervised and simple approach to local symmetry detection of ribbon-like structure in natural images. The proposed model consists in quantifying the presence of a partial medial axis segment, existing between each pair of (preliminary detected) line segments delineating the boundary of two textured regions, by a set of heuristics related both to the geometrical structure of each pair of line segments and its ability to locally delimit a homogeneous texture region in the image. This semi-local approach is finally embedded in a two-step algorithm with an amplification step, via a Hough-style voting approach achieved at different scales and coordinate spaces which aims at determining the dominant local symmetries present in the image and a final denoising step, via an averaging procedure, which aims at removing noise and spurious local symmetries. The experiments, reported in this paper and conducted on the recent extension of the Berkeley Segmentation Dataset for the local symmetry detection task, demonstrate that the proposed symmetry detector performs well compared to the best existing state-of-the-art algorithms recently proposed in the literature.